Carl R. Rogers and the Client-Centered Therapy - Arias Gallegos, Walter L. (2015)
In the present article, we make a review about the life of Carl Rogers and the theoretical development of the Client-Centered Therapy, such as a therapeutic and humanistic proposal that remarks the role of the unconditional positive regard, empathy and congruency. We comment the aspects related to the academic formation and professional influences that Rogers received